PENERAPAN METODE PROFILE MATCHING DALAM SISTEM INFORMASI SELEKSI BEASISWA PADA SMA NU 03 MUALLIMIN WELERI - Rina Silviana (LPPM Universitas Sains dan Teknologi Komputer, 2024)
Providing Scholarships is a work program that exists in every school. The scholarship program was held to ease the burden on students during their study period, especially regarding costs. Providing scholarships to students must be done selectively according to the type of scholarship being provided. Scholarships are income for those who receive them and the purpose of the scholarship is to help ease the burden of educational costs for students who receive scholarships. One of the methods used to determine potential scholarship recipients is profile matching because it is able to select the best alternative from a number of alternatives, in this case the intended alternative is those who are entitled to receive a scholarship based on specified criteria. The research was carried out by determining the aspects and sub-aspects and looking for the weight value for each sub-aspect, looking for the GAP between the profile and the state of the students' data. By using this method, the presentation of the two aspect elements is determined and added together, then a ranking process is carried out which will determine the optimal alternative, namely the student with the highest score. There are two forms of scholarship recipients used in this research, namely based on family economics and based on student attendance. The final result of this research is a decision support system for determining prospective scholarship recipients who are able to provide solutions in the form of ranking results from the Profile Matching Method selection based on predetermined criteria.